Flexclusivity: Exclusive Agreements with Competitive Flexibility - Philippe Choné; Laurent Linnemer (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Sellers face a critical choice: run competitive auctions or strike exclusive deals with preferred buyers. Contrary to conventional wisdom that sellers should rely on open competition, we show that a powerful seller optimally commits to a sequential `flexclusivity' arrangement - a strategic mix of exclusivity and competitive bidding. Under broad conditions, the seller chooses with positive probability to disregard alternative buyers entirely. We demonstrate, in a parsimonious model, that simple option contracts implement flexclusivity efficiently, increasing the expected joint profit of the contracting parties. When a preferred buyer declines the option, this credibly signals his weakness, allowing the seller to extract more rent from stronger buyers in subsequent auctions. The joint gain from such arrangements can represent as much as 75% of what vertical integration would achieve, without requiring commitment beyond the initial contracting stage.
Keywords: D44; D82; D86; L22; 330; selling mechanism; exclusivity; revenue-maximizing auction; option contract; vertical integration